Polymer-based electrolyte materials for proton exchange membrane fuel cells
Through polymer electrolyte materials based on 1,3-keto functionality, the problems of poor proton conductivity and low thermal stability of Nafion materials in proton exchange membrane fuel cells are solved, and more efficient proton conductivity and thermal stability are achieved. Reduces production costs and gas permeability.
Patent Information
- Application Number
- CN202010877212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-28
- Filing Date
- 2020-08-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-08-27
AI Technical Summary
The Nafion materials used in existing proton exchange membrane fuel cells have problems such as poor proton conductivity, low thermal stability, high gas permeability, high production costs and poor environmental compatibility. A new polymer electrolyte material is needed to replace it. .
Using polymer electrolyte materials based on 1,3-ketone functionality, through specific structural and synthetic methods, such as polycondensation reaction of diol and malonate, polymer electrolytes with improved physical, thermal and mechanical properties are prepared. Used for proton exchange membranes.
It improves the proton conductivity and thermal stability of the proton exchange membrane, reduces gas permeability, controls production costs, enhances environmental compatibility, and is suitable for fuel cell applications.
Smart Images

Figure CN112448007B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to polymer-based electrolyte materials for proton exchange membrane fuel cells. More specifically, the present disclosure relates to proton exchange membrane polymer electrolytes based on 1,3-keto functionality and methods for their production. Background Art
[0002] Fuel cells, and in particular proton exchange membrane fuel cells (PEMFCs), hold great promise as a high efficiency, high power density, relatively light weight, and zero carbon emission energy source for a variety of different applications. Such applications include, but are not limited to, transportation, stationary power generation, and portable power generation. Particularly in relation to its automotive and other transportation-related applications, PEMFCs represent an environmentally friendly alternative to internal combustion engines for a variety of vehicles.
[0003] PEMFC works based on the proton transfer between the anode and cathode. The key components of PEMFC especially include a proton exchange membrane (PEM) through which protons transfer and a membrane electrode assembly (MEA) in which the PEM is included. PEM can include polymer-based electrolyte materials that show sufficient proton conduction characteristics and acceptable thermal stability. Nafion, a sulfonated copolymer material based on tetrafluoroethylene, is a commonly used material for fuel cell PEM. Although widely used, Nafion shows relatively poor proton conductivity, low thermal stability, high gas permeability, high production cost and poor environmental compatibility. In view of such shortcomings, there is still a need for a new polymer electrolyte material that can be safely and effectively used in fuel cell PEM. Summary of the invention
[0004] According to at least one embodiment, a polymer electrolyte material having the following structure is disclosed:
[0005]
[0006] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group, Y is O, S, CH2, CHF, CF2 or NR, Z is alkylene chain, perfluoroalkylene or oxygen dialkylene, and n is an integer of 10-1000. According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl. According to the embodiment in which X is a polar group, non-limiting examples include F, CN, SO2, C (O) Me, C (O) Et, CO2Me and CO2Et. According to the embodiment in which X is a perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3. According to the embodiment in which X is an olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2). According to the embodiment where X is an alkoxy group, non-limiting examples include methoxy (-OCH3), ethoxy (-OCH2CH3), propoxy (-OCH2CH2CH3). In certain embodiments, crosslinked and non-crosslinked block copolymer electrolytes containing dicarbonyl polymer electrolyte materials are disclosed, such as those described by the structures shown above.
[0007] In another embodiment, a proton exchange membrane (PEM) for a proton exchange membrane fuel cell (PEMFC) is disclosed. The PEM comprises a polymer electrolyte material having the following structure:
[0008]
[0009] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group, Y is O, S, CH2, CHF, CF2 or NR, Z is alkylene chain, perfluoroalkylene or oxygen dialkylene, and n is an integer in the range of 10-1000. According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl. According to the embodiment in which X is a polar group, non-limiting examples include F, CN, SO2, C(O)Me, C(O)Et, CO2Me and CO2Et. According to the embodiment in which X is a perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3. According to the embodiment in which X is an olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2). According to the embodiment where X is alkoxy, non-limiting examples include methoxy (-OCH3), ethoxy (-OCH2CH3), propoxy (-OCH2CH2CH3), and the like.
[0010] According to other embodiments, a method for producing a polymer electrolyte material for a proton exchange membrane is disclosed. The method involves the polycondensation of a diol with a malonate. In one embodiment, the malonate can be dimethyl malonate. According to at least one embodiment, the synthesis of certain dicarbonyl polymer electrolyte materials disclosed herein can be defined as follows:
[0011]
[0012] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group, and Z is alkylene chain, perfluoroalkylene or oxygen dialkylene group.According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl.According to the embodiment in which X is polar group, non-limiting examples include F, CN, SO2, C(O)Me, C(O)Et, CO2Me and CO2Et.According to the embodiment in which X is perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3.According to the embodiment in which X is olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2).According to the embodiment in which X is alkoxyl group, non-limiting examples include methoxyl group (-OCH3), ethoxyl group (-OCH2CH3), propoxyl group (-OCH2CH2CH3) etc.
[0013] The size and properties of the diols can be varied to control the physical, thermal and mechanical properties of the resulting polymer electrolyte. For example, according to certain embodiments, bulky diols such as adamantane diol can be introduced into the polycondensation reaction to produce a polymalonate electrolyte having a high glass transition temperature. In addition, the acidity and proton conductivity of the resulting polymalonate electrolyte can also be altered by varying the polarity and size of the diols used in the polycondensation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic depiction of a proton exchange membrane fuel cell including a membrane electrode assembly is shown. DETAILED DESCRIPTION
[0015] Embodiments of the present disclosure are described below. However, it should be understood that the disclosed embodiments are only examples, and other embodiments may take various and alternative forms. The drawings are not necessarily to scale; some features may be exaggerated or minimized to show the details of a particular component. Therefore, the specific structural and functional details disclosed herein should not be interpreted as restrictive, but only as a representative basis for teaching those skilled in the art to use the present invention in various ways. As will be understood by those of ordinary skill in the art, the various features shown and described with reference to any one of the figures may be combined with the features shown in one or more other figures to produce embodiments that are not explicitly shown or described. The combination of the features shown provides representative embodiments for typical applications. However, various combinations and modifications of features consistent with the teachings of the present disclosure may be desirable for specific applications or implementations.
[0016] The description of a group or class of materials as suitable for a given purpose in connection with one or more embodiments means that mixtures of any two or more members of the group or class are suitable. Descriptions of ingredients in chemical terms refer to the ingredients at the time of addition to any combination listed in the specification and do not necessarily preclude chemical interactions between the ingredients of the mixture once mixed.
[0017] Except where expressly indicated, all numerical quantities expressing dimensions or material properties in this specification are to be understood as being modified by the word "about" in describing the broadest scope of the present disclosure.
[0018] The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein and applies mutatis mutandis to normal grammatical variations of the originally defined abbreviation. Unless expressly stated to the contrary, measurements of properties are determined by the same techniques as previously or later cited for the same property.
[0019] Reference is made in detail to compositions, embodiments, and methods of embodiments known to the inventors. However, it should be understood that the disclosed embodiments are merely examples of the present invention, which can be implemented in various and alternative forms. Therefore, the specific details disclosed herein should not be interpreted as limiting, but only as a representative basis for teaching those skilled in the art to use the present invention in various ways.
[0020] The terms "substantially" or "approximately" may be used herein to describe the disclosed or claimed embodiments. The terms "substantially" or "approximately" may modify a value or relative property disclosed or claimed in the present disclosure. In this case, "substantially" or "approximately" may mean that the value or relative property it modifies is within ±0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or 10% of the value or relative property.
[0021] Proton exchange membrane fuel cells (PEMFCs) are of interest for use in a variety of applications due to their high efficiency and high power density in addition to their relatively light weight and zero carbon emissions. In the membrane electrode assembly (MEA) of a PEMFC, protons are transferred from the anode to the cathode through a proton exchange membrane (PEM). A PEM is a polymer-based electrolyte material that exhibits adequate proton-conducting properties. Due to this primary function, PEMs are also called cation exchange membranes and typically comprise proton-conducting polymer membranes. In view of their proton-conducting role, acidic functionality - like that of carboxylic acids, sulfonic acids, and phenolic acids - is often a key characteristic of PEMs and their associated polymer electrolyte materials. In addition to the ability to conduct protons efficiently, suitable PEMs and their associated polymer electrolyte materials must also exhibit adequate thermal stability in a PEMFC environment.
[0022] Nafion, a sulfonated - and fully fluorinated - ion conducting polymer based on tetrafluoroethylene, is commonly used in fuel cell PEMs. However, Nafion exhibits relatively poor proton conductivity, low thermal stability, high gas permeability, high production costs, and poor environmental compatibility. Therefore, new ion conducting polymer materials - and PEMs made therefrom - are of interest for addressing one or more of these or other disadvantages associated with the use of Nafion in fuel cells. The present disclosure describes polymer electrolyte materials based on 1,3-keto functionality and methods for producing the same. In one or more embodiments, the polymer electrolyte may be generally described as a poly(1,3-dicarbonylalkane) material.
[0023] A non-limiting example of a PEMFC is depicted in Figure 1 In, it may include the PEM and related polymer electrolyte materials disclosed herein. The core component of the PEMFC 10 is the membrane electrode assembly (MEA) 12, which facilitates the electrochemical reactions within the stack. The MEA 12 includes a PEM through which protons are transferred. As already described, the PEM typically contains a polymer-based electrolyte material such as Nafion. In addition to the PEM, the MEA 12 also includes other subcomponents such as electrodes and catalysts. Within the MEA 12, protons are transferred from the anode to the cathode through the PEM and its related polymer electrolyte. The electrodes can be made of any suitable material and can be hot pressed onto the PEM within the MEA 12. The anode and cathode electrodes typically also contain a catalyst layer that contains a platinum group metal such as platinum or ruthenium. In addition to the MEA 12 and its various subcomponents, the PEMFC 10 also typically includes other components such as a current collector 14, (one or more) gas diffusion layers 16, a gasket 18 and at least one bipolar plate (BPP) 20.
[0024] According to certain embodiments, a polymer electrolyte material based on 1,3-keto functionality is disclosed, which is suitable for use in PEMFC. In one or more embodiments, such a polymer electrolyte can be defined by the following general structure (I):
[0025] (I),
[0026] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group, Y is O, S, CH2, CHF, CF2 or NR, Z is alkylene chain, perfluoroalkylene or oxygen dialkylene, and n is an integer in the range of 10-1000. According to the embodiment in which Y is NR, R can be any alkyl, such as but not limited to alkyl or aryl. According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl. According to the embodiment in which X is a polar group, non-limiting examples include F, CN, SO2, C(O)Me, C(O)Et, CO2Me and CO2Et. According to the embodiment in which X is a perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3. According to the embodiment in which X is an olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2). According to the embodiment where X is alkoxy, non-limiting examples include methoxy (-OCH3), ethoxy (-OCH2CH3), propoxy (-OCH2CH2CH3), and the like.
[0027] According to the present invention, the polymer electrolyte of general structure (I) can contain various substituents such as X, Y and Z. In view of the main proton conduction of PEM, suitable polymer electrolyte materials according to the present disclosure can be specifically selected based on the acidic function of the polymer. If X is H in the polymer electrolyte of general structure (I), at least two acidic protons will exist in each repeating unit. However, if X is not H, only one acidic proton can exist in each repeating unit. By changing the properties of the substituent X, the acidity of the CH proton between the two carbonyl groups can also be manipulated. In malonate, for example, where Y is O according to general structure (I), the pKa of the active proton can be adjusted by selecting component X. As shown in Table 1 below, when X is changed from an electron-donating group methyl to an electron-withdrawing group CF3, the acidity of the active proton increases. This is demonstrated in Table 1 by the relevant pKa being reduced from 18 to 10.8. Therefore, the malonate substituted with CF3 is more acidic than acetic acid with a pKa of 12.6.
[0028] Table 1
[0029] Comparison of pKa values of various substituted malonates
[0030] .
[0031] As shown in Table 2 below, the pKa of the active proton can also be adjusted by selecting ingredient Y in the 1,3-dicarbonyl polymer of general structure (I). This is demonstrated by the data shown in Table 2 below, where Y is an alkyl group and / or a chain instead of O. In the simplified example where Y is CH3, the pKa values of the active protons within the resulting 1,3-diketone repeating unit are different from those shown in Table 1 for substituted malonate repeating units. According to the data shown in Tables 1 and 2, when comparing structures with the same substituent X, 1,3-diketone-based repeating units are generally more acidic than malonate-based repeating units. For example, when X is H, Table 2 shows that the resulting 1,3-diketone repeating unit has a pKa of 13.3, while Table 1 shows that the resulting malonate repeating unit has a pKa of 15.9. Also as shown in Table 2, when X changes from an electron-donating group methyl to an electron-withdrawing group acetyl, the acidity of the active proton increases. This is demonstrated by the reduction of the relevant pKa from 15.1 to 8.6 shown in Table 2.
[0032] Table 2
[0033] Comparison of pKa values of various substituted 1,3-diketones
[0034] .
[0035] The pKa values shown in Tables 1 and 2 were calculated by pKa prediction software. The specific software used for the calculations is from ACDlabs, which utilizes a database of over 17,000 structures and Hammet-type equations for ionizable functional groups to predict accurate pKa values.
[0036] In one or more embodiments, the polymer electrolyte of general structure (I) may include: H, CH3, CH2CH3, CO2Me, CF3 or CH3CO as X; O or alkyl as Y; alkylene chain as Z; and n may be in the range of 10-1000. According to at least one embodiment, the polymer electrolyte of general structure (I) includes CF3 as X, CH2 as Y, CH3 ... 10 As Z. As described in more detail below, according to certain embodiments, a polymer electrolyte of general structure (I) is disclosed, which comprises an olefinic group in a polymer side chain, i.e., as X, or in a polymer backbone, i.e., as Y and / or Z. In one or more embodiments, both X and Y comprise an olefinic group. In other embodiments, both X and Z comprise an olefinic group. In still other embodiments, both Y and Z comprise an olefinic group. In still other embodiments, each of X, Y and Z comprises an olefinic group.
[0037] According to certain embodiments, the polymer electrolyte defined by the general structure (I) shown above can be used for the proton exchange membrane of PEMFC. The PEM based on the 1,3-dicarbonyl repeating unit described herein can be a solid or semi-solid membrane and can have various thicknesses. According to at least one embodiment, the thickness of the PEM polymer electrolyte membrane is 10μm-0.5 mm. According to other embodiments, the thickness of the PEM polymer electrolyte membrane is 20μm-300μm. In still other embodiments, the thickness of the PEM polymer electrolyte membrane is 50μm-200μm. In still other embodiments, the thickness of the PEM polymer electrolyte membrane is 100μm-150μm.
[0038] The polymer electrolytes defined by the general structure (I) and suitable for use as PEMs can be characterized by various molecular weights. According to one or more embodiments, suitable polymers can include molecular weights of 1000 g / mol to 1000000 g / mol. In other embodiments, the molecular weight of the polymer electrolyte material is 2000 to 200000 g / mol. In yet other embodiments, the molecular weight of the polymer electrolyte material is 5000 g / mol to 20000 g / mol.
[0039] The PEM based on the 1,3-dicarbonyl repeating unit polymer described herein comprises a semipermeable membrane having a first proton conductivity in an unstretched configuration and having an equal or increased proton conductivity in a stretched configuration. In its unstretched configuration, the polymer electrolyte membrane disclosed herein is not physically stretched in any dimension after forming. In its stretched configuration, the polymer electrolyte membrane disclosed herein is physically stretched in at least one dimension after forming.
[0040] There are various suitable methods for producing polymer electrolyte materials defined by general structure (I) for proton exchange membranes. Examples of such methods involve polycondensation of diols with malonates. In at least one embodiment, the malonate used in the polycondensation reaction is dimethyl malonate. In another embodiment, the malonate is diethyl malonate. Example synthetic reactions that can produce certain polymer electrolyte materials defined by general structure (I) include the general transesterification reaction (A) shown below:
[0041]
[0042] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group, and Z is alkylene chain, perfluoroalkylene or oxygen dialkylene group.According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl.According to the embodiment in which X is polar group, non-limiting examples include F, CN, SO2, C(O)Me, C(O)Et, CO2Me and CO2Et.According to the embodiment in which X is perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3.According to the embodiment in which X is olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2).According to the embodiment in which X is alkoxyl group, non-limiting examples include methoxyl group (-OCH3), ethoxyl group (-OCH2CH3), propoxyl group (-OCH2CH2CH3) etc. In the example transesterification reaction (A) shown above, a polymalonate, wherein Y is O according to general structure (I), is synthesized from dimethyl malonate and a diol in the presence of methanol and an acid catalyst.
[0043] In one example, the synthesis of poly-[pentyl fluoromalonate] is as follows. In an argon atmosphere, a solution of titanium (IV) isopropoxide (0.07 mL, 0.23 mmol) is added to a solution (10 mL) of diethyl fluoromalonate (4.2 g, 23.4 mmol) and 1,5-pentanediol (2.4 g, 23.4 mmol) in THF, and the mixture is stirred at 120 ° C for 2 hours. While maintaining the same temperature, the reaction flask is intermittently exposed to high vacuum for 5 hours to remove the ethanol that appears from the reaction mixture. Similarly, at the same temperature, the partially polymerized mixture in the reaction flask is exposed to a constant high vacuum for 24 hours. The viscous polymerization mixture is then dissolved in dichloromethane and added dropwise to a large volume (100 mL) of stirred methanol to obtain poly-[pentyl fluoromalonate] (yield 4.7 g, 85%).
[0044] According to the general transesterification reaction (A) shown above, the size and properties of the diol can be varied to control the physical, thermal and mechanical properties of the resulting polymer electrolyte. For example, according to certain embodiments, a bulky diol such as adamantane diol can be introduced into the polycondensation reaction to produce a polymalonate electrolyte with a high glass transition temperature. In addition, the acidity and proton conductivity of the resulting polymalonate electrolyte can also be changed by changing the polarity and size of the diol used in the polycondensation reaction. For example, longer diols will result in a decrease in the acid functionality density of the polymer and therefore a decrease in proton conductivity.
[0045] By introducing olefinic groups into the polymer electrolyte of general structure (I), free radicals or thiol-ene chemistry can be used to make the polymer cross-linked. According to embodiments of the present disclosure, olefinic groups can be included in the general structure (I) polymer with side chains, i.e. as X, or with polymer backbones, i.e. as Y and / or Z. In some embodiments, olefinic groups are included in the side chains or backbones of the polymer electrolyte of general structure (I), but are not included in both. In other embodiments, olefinic groups are included in both the side chains and backbones of the polymer electrolyte of general structure (I). In at least one embodiment, substituents X, Y and Z each include olefinic groups. For example, when olefinic groups such as allyl (-CH2CH=CH2) are X and O is Y in the polymer electrolyte of general structure (I), the polymer electrolyte of general structure (II) can be defined as follows:
[0046] (II)
[0047] Wherein Z is an alkylene chain, a perfluoroalkylene chain or an oxydialkylene chain. Alternatively, such an olefin-containing polymer electrolyte material may contain any type of olefinic group in the range of 2 to 10 carbon atoms as a substituent X. Similarly, for example, when an olefinic group such as -CH2CH=CHCH2 is Z and O is Y in a polymer electrolyte of general structure (I), a polymer electrolyte of general structure (III) may be defined as follows:
[0048] (III)
[0049] Wherein X is H, alkyl, polar group, perfluoro group, olefinic group or alkoxyl group.According to the embodiment in which X is alkyl, non-limiting examples include methyl, ethyl, isopropyl, butyl and tert-butyl.According to the embodiment in which X is polar group, non-limiting examples include F, CN, SO2, C(O)Me, C(O)Et, CO2Me and CO2Et.According to the embodiment in which X is perfluoro group, non-limiting examples include CF3, CF2CF3 and CH2CF3.According to the embodiment in which X is olefinic group, non-limiting examples include vinyl (-CH=CH2) and allyl (-CH2CH=CH2).According to the embodiment in which X is alkoxyl group, non-limiting examples include methoxyl group (-OCH3), ethoxyl group (-OCH2CH3), propoxyl group (-OCH2CH2CH3) etc.Or, such olefin-containing polymer electrolyte material can include any type of olefinic group in which carbon number is 2-10 scope as substituent Z.
[0050] According to one or more embodiments, the polymer electrolyte defined by the general structures (II) and (III) shown above can be used for the proton exchange membrane of PEMFC. Such a polymer electrolyte can be cross-linked or non-cross-linked and can form membranes of various thicknesses. According to at least one embodiment, the thickness of the PEM polymer electrolyte membrane is 10μm-0.5mm. According to other embodiments, the thickness of the PEM polymer electrolyte membrane is 20μm-300μm. In still other embodiments, the thickness of the PEM polymer electrolyte membrane is 50μm-200μm. In still other embodiments, the thickness of the PEM polymer electrolyte membrane is 100μm-150μm.
[0051] Olefin-containing polymer electrolyte materials, such as those defined by general structures (II) and (III), can be crosslinked using free radical or thiol-ene chemistry. For free radical-induced crosslinking, a small amount of a free radical initiator such as AIBN or peroxide can be added to the dicarbonyl polymer film to form a crosslinked polymer. For thiol-ene type crosslinking, a small amount of trithiol or dithiol can be used in the reaction.
[0052] According to certain embodiments, the dicarbonyl polymer electrolyte materials disclosed herein, such as those defined by the general structures (I), (II) and (III), can be used to form crosslinked and non-crosslinked block copolymers used as PEMs. In such a configuration, the proton conducting block of the block copolymer may include one or more of the dicarbonyl polymer electrolyte materials disclosed herein. The mechanical block of the copolymer may include, for example, polystyrene, polyphenylene ether (PPE) or any other suitable material. In such an embodiment, the block copolymer may be crosslinked at the mechanical block or at the conductive block. A non-limiting example of a block copolymer comprising a dicarbonyl polymer electrolyte disclosed herein as a conductive block, in this embodiment poly (1,3-nonyldione), and styrene as a mechanical block can be defined by the following structure (IV):
[0053] (IV),
[0054] wherein m is an integer in the range of 1 to 10000, and n is an integer in the range of 10 to 1000. Although the polymer electrolyte material of structure (IV) is based on poly(1,3-nonyldione), it should be understood that any polymer electrolyte defined by general structures (I), (II) or (III) may be used according to certain embodiments.
[0055] The block copolymer electrolyte suitable for use as a proton exchange membrane for PEMFC comprises at least a first block comprising a dicarbonyl polymer defined by the general structure (I) and a first block comprising a dicarbonyl polymer having a molecular weight of more than 1×104 In some embodiments, the second polymer block may have a tensile modulus of 10 Pa at a temperature of 150° C. and below. 4 -10 9 In other embodiments, the second polymer block may have a modulus of 10 Pa at a temperature of 150° C. and below. 5 -10 8 The modulus of Pa. Non-limiting examples of polymers included in the second block include polystyrene, hydrogenated polystyrene, polymethacrylate, poly(methyl methacrylate), polyvinylpyridine, polyvinylcyclohexane, polyimide, polyamide, polypropylene, poly(2,6-dimethyl-1,4-phenylene ether) (PXE), polyolefin, poly(tert-butyl vinyl ether), poly(cyclohexyl methacrylate), poly(cyclohexyl vinyl ether), polyethylene, fluorocarbon, polyvinylidene fluoride and copolymers containing styrene, methacrylate and / or vinylpyridine. In some configurations, the first block, which contains a dicarbonyl polymer, forms the proton conducting phase of the block copolymer, and the second block forms the structural phase of the block copolymer. In addition to such a diblock configuration, the block copolymer disclosed herein can also be a triblock copolymer electrolyte. In a triblock configuration comprising the above first and second blocks, the third block may comprise another dicarbonyl polymer or a mechanopolymer defined by general structure (I) and thereby form a proton conducting phase or a structural phase within the block copolymer.
[0056] The size or width of the conductive phase and the structural phase can be adjusted by adjusting the molecular weight of each polymer block. According to at least one embodiment, the characteristic size of the phase is 5nm-1000nm. According to other embodiments, the characteristic size of the phase is 10nm-500nm. In other embodiments, the characteristic size of the phase is 10nm-200nm. In other embodiments, the characteristic size of the phase is 15nm-100nm. In various embodiments, depending on the properties of the polymer blocks and their ratios in the block copolymer, the phase can be lamellar, cylindrical, spherical or helical. In diblock and triblock configurations, the blocks can all be covalently bonded together.
[0057] In some diblock configurations, both the first block and the second block are linear polymer blocks. In other diblock configurations, one or both blocks have a comb-shaped (or branched) structure. In one diblock configuration, neither block is cross-linked. In another diblock configuration, one block is cross-linked. In yet another diblock configuration, both blocks are cross-linked.
[0058] In some triblock configurations, the first block, the second block, and the third block are each a linear polymer block. In other triblock configurations, one or more of the blocks have a comb-shaped (or branched) structure. In one triblock configuration, none of the blocks are crosslinked. In another triblock configuration, one block is crosslinked. In yet another triblock configuration, two blocks are crosslinked. In yet another triblock configuration, all three blocks are crosslinked.
[0059] Although exemplary embodiments are described above, it is not intended that these embodiments describe all possible forms of the present invention. On the contrary, the words used in the specification are descriptive rather than restrictive, and it should be understood that various changes may be made without departing from the spirit and scope of the present invention. In addition, the features of various embodiments may be combined to form further embodiments of the present invention.
Claims
1. A proton exchange membrane for a proton exchange membrane fuel cell, comprising: A proton conducting polymer having a polymer structure as described below: in X is an alkyl group, a perfluoro group, an olefinic group or an alkoxy group; Y is O, S, CH2, CHF, CF2 or NR, wherein R is a hydrocarbon group; Z is an alkylene chain, a perfluoroalkylene chain or an oxydialkylene chain; n is an integer in the range of 10-1000; and The proton conducting polymer has a thickness of 10 μm to 0.5 mm. 2 . The proton exchange membrane according to claim 1 , wherein the proton conductive polymer has a thickness of 20 μm to 300 μm.
3. The proton exchange membrane of claim 1, wherein the proton conducting polymer forms a first polymer block of a block copolymer material and the proton exchange membrane further comprises a second polymer block in the block copolymer material.
4. The proton exchange membrane according to claim 3, wherein the second polymer block has 10 4 -10 9 The modulus of Pa.
5. The proton exchange membrane of claim 4, wherein the first and second polymer blocks are linear polymer blocks. The proton exchange membrane according to claim 4 , wherein the second polymer block comprises polystyrene or polyphenylene ether.
7. The proton exchange membrane of claim 4, wherein the block copolymer material is cross-linked at the first polymer block.
8. The proton exchange membrane according to claim 4, wherein the block copolymer material has a thickness of 10 μm to 0.5 mm.
9. The proton exchange membrane of claim 4, further comprising a third polymer block in the block copolymer material.
10. The proton exchange membrane according to claim 9, wherein the third polymer block comprises a proton conducting polymer having a polymer structure described below: in X is H, an alkyl group, a polar group, a perfluoro group, an olefinic group or an alkoxy group; Y is O, S, CH2, CHF, CF2 or NR, wherein R is a hydrocarbon group; and Z is an alkylene chain, a perfluoroalkylene chain or an oxydialkylene chain.
11. The proton exchange membrane according to claim 1, wherein X in the polymer structure is CF3, an alkyl group or an olefinic group.
12. The proton exchange membrane according to claim 1, wherein Y in the polymer structure is O or CH2 and Z is C5H 10 .
13. The proton exchange membrane of claim 1, wherein the polymer is cross-linked.
14. The proton exchange membrane of claim 1, wherein the polymer has a molecular weight of 1000 g / mol to 1000000 g / mol.
15. The proton exchange membrane of claim 1, wherein the polymer is prepared by polycondensation of dimethyl malonate and diol.
16. The proton exchange membrane according to claim 15, wherein the dimethyl malonate has the structure described below: wherein X is an alkyl group, a perfluoro group, an olefinic group or an alkoxy group.
17. The proton exchange membrane according to claim 15, wherein the diol has a structure described below: HO-Z-OH wherein Z is an alkylene chain, a perfluoroalkylene chain or an oxydialkylene chain.
18. The proton exchange membrane of claim 15, wherein the polycondensation comprises stirring a mixture of dimethyl malonate and diol at a temperature of 90°C to 140°C for 1 to 5 hours.
19. The proton exchange membrane of claim 15, wherein the polycondensation comprises exposing a mixture of dimethyl malonate and a diol to a vacuum at a temperature of 90°C to 140°C.
Citation Information
Patent Citations
Nonaqueous electrolyte solution and lithium secondary battery using same
CN101091283A
Electrolytic solution and device for generating electric energy therewith
CN1229529A
Diester-based polymer electrolytes for high voltage lithium ion batteries
US20180294521A1
